Articulatory feature-based pronunciation modeling. (March 2016) - Livescu, Karen; Jyothi, Preethi; Fosler-Lussier, Eric
Abstract : Highlights: We review our research developing articulatory feature-based pronunciation models. We argue for sub-phonetic features inspired by articulatory phonology. We review evaluations via frame-level perplexity and lexical access performance. Our models typically outperform phone-based models. Context-dependent surface feature models outperform context-independent models. Abstract: Spoken language, especially conversational speech, is characterized by great variability in word pronunciation, including many variants that differ grossly from dictionary prototypes. This is one factor in the poor performance of automatic speech recognizers on conversational speech, and it has been very difficult to mitigate in traditional phone-based approaches to speech recognition. An alternative approach, which has been studied by ourselves and others, is one based on sub-phonetic features rather than phones. In such an approach, a word's pronunciation is represented as multiple streams of phonological features rather than a single stream of phones. Features may correspond to the positions of the speech articulators, such as the lips and tongue, or may be more abstract categories such as manner and place. This article reviews our work on a particular type of articulatory feature-based pronunciation model. The model allows for asynchrony between features, as well as per-feature substitutions, making it more natural to account for many pronunciation changes that are difficult to handle with phone-based models. Such models can be efficiently represented as dynamic Bayesian networks. The feature-based models improve significantly over phone-based counterparts in terms of frame perplexity and lexical access accuracy. The remainder of the article discusses related work and future directions.